Physiological and functional characteristics of Propionibacterium strains of the poultry microbiota and relevance for the development of probiotic products - Argañaraz Martínez, Fernando Eloy (2013)
The prevention and control of pathogens colonization through probiotics administration in poultry feeding is of increasing interest. The genus Propionibacterium is an attractive candidate for the development of probiotic cultures as they produce short chain fatty acids (SCFA) by carbohydrates fermentation. The presence of strains of this genus in hens of conventional production systems and backyard hens was investigated. Propionibacteria were isolated from the intestine and identified by physiological and biochemical tests. PCR amplification of the 16S rRNA gene of the isolates was performed and products were compared with sequences from databases. The genus Propionibacterium was demonstrated in 26 % of hens and P. acidipropionici and P.avidum were the species identified. A comparative study of their physiological and functional characteristics was performed. P.acidipropionici strains were the most resistant to in vitro gastrointestinal digestion, but the adhesion to intestinal tissue was strain dependent. Some differences were found between both species with respect to their growth and SCFA production in an in vitro cecal water model, but all the strains were metabolically active. The production of SCFA in homogenates of cecal content inoculated with P.acidipropionici LET105 was 30 % higher than in non inoculated homogenates. SCFA concentrations obtained were high enough to inhibit Salmonella enterica serovar Enteritidis when assayed in a cecal water model. P.acidipropionici LET105 was also able to compete with Salmonella for adhesion sites on the intestinal mucosa in ex vivo assays. Results contribute to the knowledge of the physiology of propionibacteria in the intestine of poultry and provide evidence of their potential for probiotics products development.